Anti-cyclic citrullinated peptide antibody related to the disease progression and extra-articular involvement in patient with rheumatoid arthritis in Hospital Universiti Sains Malaysia - Sulaiman, Farah Nadiah (2017)
BACKGROUND : Rheumatoid arthritis (RA) is a chronic debilitating inflammatory disease affecting mainly the joint and surrounding tissue, and also involved other extra articular structures in the body. It can lead to destruction of bone and cartilage which may cause severe disability to the patient. Other than rheumatoid factor, anti-cyclic citrullinate peptide (anti-CCP) antibody is another biomarker that can be used to diagnose RA with higher sensitivity and specificity. OBJECTIVE : To evaluate the significant of anti-CCP antibody in predicting the disease activity, and disease progression in term of radiological and extra articular manifestation upon diagnosis in patient with rheumatoid arthritis in HUSM. METHODS : This was a cross sectional study with retrospective record review. A total of 159 patients who were diagnosed as rheumatoid arthritis based on 2010 EULAR criteria for RA since 2010 until 2017 under rheumatology clinic HUSM follow up were included in this study. Exclusion criteria include age of 16 years old or less at the onset of diagnosis, probable RA, and overlap syndromes or related to other connective tissue disease. The data was retrieved from medical record for rheumatoid factor, anti-CCP antibody, assessment of disease activity using DAS28 ESR calculator, plain radiograph of hands or feet, and extra-articular manifestation in term ofassessment of rheumatoid nodule, pulmonary involvement, Felty syndrome, vasculitis and anemia upon diagnosis. RESULTS : From a total of 159 patients, 134 (84.3%) patients were female with majority ethnic group was Malay (87.4%). The mean for age was 48.3 years old; ranging from 17 to 79. The prevalence of anti-CCP antibody was 52.2% (95% CI 0.44 to 0.60) and the percentage of positive rheumatoid factor was 62.3%. Mean DAS28-ESR score for total patients was 4.74 which medium and high disease activity were predominant upon diagnosis. 36.5% of patients had radiological involvement and 30.8% of patients had extra-articular involvement manifested by rheumatoid nodule, pulmonary involvement, and anemia. Patients with both positive rheumatoid factor and anti-CCP antibody was significantly higher than other groups (n=83; 73.5%) (p-value 0.002). For radiological involvement, it was significantly higher in anti-CCP antibody positive group. However, there was no significant difference between mean and classes of disease activity score, and extra-articular manifestations between different anti-CCP antibody positivity group. Extra-articular manifestations was not associated with high disease activity upon diagnosis of RA. CONCLUSION : In conclusion, there was significant association between anti-CCP antibody positivity and positive rheumatoid factor and radiological involvement, however no significant difference found in mean disease activity and extra-articular manifestation upon diagnosis in patient withRA in HUSM. Extra-articular manifestations was not associated with high disease activity upon diagnosis of RA.